2018
DOI: 10.1007/s12369-017-0458-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Robotic Tutors that Support Self-Regulated Learning: A Longer-Term Investigation with Primary School Children

Abstract: Robots are increasingly being used to provide motivating, engaging and personalised support to learners. These robotic tutors have been able to increase student learning gain by providing personalised hints or problem selection. However, they have never been used to assist children in developing self regulated learning (SRL) skills. SRL skills allow a learner to more effectively self-assess and guide their own learning; learners that engage these skills have been shown to perform better academically. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 40 publications
0
43
0
1
Order By: Relevance
“…In this individual learning scenario, breakdowns in the interaction were associated with "the robot's inability to evoke initial engagement and identify misunderstandings, confusing scaffolding, lack of consistency and fairness, and controller problems." In another long-term study in which a robot acted as an agent for learning, Jones and Castellano [2018] concluded that if a robot provides personalized and adapted scaffolding to students based on their learning, they can better regulate their own learning . Furthermore, in a study of two consecutive weeks in a school, a peer-robot that exhibited behavioural personalization was found to have a positive influence on learning when interacting with children, compared to a robot that exhibited non-personalization.…”
Section: Robots In Educationmentioning
confidence: 99%
“…In this individual learning scenario, breakdowns in the interaction were associated with "the robot's inability to evoke initial engagement and identify misunderstandings, confusing scaffolding, lack of consistency and fairness, and controller problems." In another long-term study in which a robot acted as an agent for learning, Jones and Castellano [2018] concluded that if a robot provides personalized and adapted scaffolding to students based on their learning, they can better regulate their own learning . Furthermore, in a study of two consecutive weeks in a school, a peer-robot that exhibited behavioural personalization was found to have a positive influence on learning when interacting with children, compared to a robot that exhibited non-personalization.…”
Section: Robots In Educationmentioning
confidence: 99%
“…Opening up such an internal knowledge base of a system to the user is commonly referred to as an open learner model [11] or system transparency [58,59,61]. Open learner models often take the form of a series of skill meters [10,38,39,57] and have been shown to help students to better regulate their efforts [10] or to improve their problem selection [63]. Transparency about system states has further been demonstrated to enhance trust in the system as a whole by making its behavior more understandable [58,59,61] and, therefore, reducing uncertainty in the user.…”
Section: Scaffolding and Transparency Through Robot's Explanationmentioning
confidence: 99%
“…Several studies involving personalized robots in learning have also explored methods to sustain engagement for students, for example, by leveraging attention data from wearable sensors [50] or by employing multi-activity switching over the course of several interactions [11]. More recent work has gone farther by investigating a robot tutor that provides personalized feedback and encourages students to build self-regulated learning skills over multiple sessions, demonstrating that students who interacted with the personalized robot that provided scaffolding were able to more successfully enhance their self-regulated learning skills [25]. These studies address the effects of various supportive mechanisms within a learning interaction, whereas our work aims to understand the effect of content-based personalization with a robot tutor over multiple sessions on learning outcomes.…”
Section: Personalized Robot Tutoringmentioning
confidence: 99%